Development a hyaluronic acid ion-pairing liposomal nanoparticle for enhancing anti-glioma efficacy by modulating glioma microenvironment - Liuqing Yang; Xu Song; Ting Gong; Kejun Jiang; Yingying Hou; Tijia Chen; Xun Sun; Zhirong Zhang; Tao Gong (Taylor & Francis Group, 2018)
Glioma, one of the most common brain tumors, remains a challenge worldwide. Due to the specific biological barriers such as blood-brain barrier (BBB), cancer stem cells (CSCs), tumor associated macrophages (TAMs), and vasculogenic mimicry channels (VMs), a novel versatile targeting delivery for anti-glioma is in urgent need. Here, we designed a hyaluronic acid (HA) ion-pairing nanoparticle. Then, these nanoparticles were encapsulated in liposomes, termed as DOX-HA-LPs, which showed near-spherical morphology with an average size of 155.8 nm and uniform distribution (PDI = 0.155). HA was proven to specifically bind to CD44 receptor, which is over-expressed on the surface of tumor cells, other associated cells (such as CSCs and TAMs) and VMs. We systematically investigated anti-glioma efficacy and mechanisms in vivo and in vitro. The strong anti-glioma efficacy could attribute to the accumulation in glioma site and the regulation of tumor microenvironment with depletion of TAMs, inhibition of VMs, and elimination of CSCs.